PENGARUH KEPEMIMPINAN DAN KEMAMPUAN SDM TERHADAP EFEKTIVITAS PELAYANAN PENSERTIFIKATAN HAK ATAS TANAH PADA KANTOR PERTANAHAN KOTA TANGERANG - Hadiwijaya, Dudung; Fazira, Rabitha (Universitas Muhammadiyah Tangerang, 2018)
The purpose of the research is to examine the influence of the leadership and HR ability to the service effectiveness of the land property rights at Agrarian Office of Tangerang City. The result of the research indicate that the leadership and HR ability are together have significant effect toward service effectiveness. The result also indicates that the leadership have more dominant and significant effect than HR ability towards the service effectiveness of the land property rights at Agrarian Office of Tangerang City. Keywords: the leadership, HR ability, service effectiveness